Analyses of the urban life quality from the perspective of public leisure spaces - Oliveira, Lucimara Albieri de (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This research work analyses the quality of urban life from the point of view of leisure public spaces through a case study in the city of Passo Fundo, State of Rio Grande do Sul. Those spaces were classified in typologies (parks, public squares, plazas and yards), and their evolution through several years were investigated. They were also analysed in quantitative terms, and according to the existing infra structure, equipment, urban furniture, conservation and maintenance state, comparing with their spatial distribution and population density. A reflection on urban planning is made, investigating how such public spaces could contribute to environmental and urban qualification of the town, as elements of urban planning and design. Urban quality depends on existing leisure public spaces, considering both their quantity and quality. It means that it is not enough to quantify them, but it is also necessary to have a more detailed understanding about the quality of those spaces, and whether they fulfil the needs of the population equally. The introduction or the optimization of those spaces in urban areas is a major challenge, considering the transformation of social demands, legal limits of the State, and the real estate market influences. Therefore, the disordered city growth and the management policies, which do not always consider community needs, may affect the distribution, typology and maintenance of leisure public spaces, benefiting only a small part of the population.